Uji Validitas InstrumenLearning Progression Konsep Biodiversitas pada Siswa Kelas X dan XI SMA Negeri di Surakarta - Safina Salma; Murni Ramli; Nurmiyati Nurmiyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
The research aims to test and find out: 1) the validity of the instruments made from Learning Progression of grade X and XI students of SMA Negeri in Surakarta against the concept of biodiversity material. 2) Profile of the concept understanding of class X and XI students of SMA Negeri in Surakarta towards the concept of biodiversity material. This research is an ex post facto study with a survey method using unchanged variables, namely class and gender. The study population was all students of class X and XI of SMA Negeri in Surakarta. The sample in this study was 274 students. The sampling technique uses random sampling to select schools and convenience in nature to choose class samples. The research data in the form of written test results of students with the Order Multiple Choice (OMC) type with instrument instruments compiled refer to the Learning Progression of Diversity map from the National Research Council (NRC) in 2007. Data collection using the test method.Data validation using Pearson product moment correlation techniques. Analysis of the data used is Pearson product moment correlation and item analysis. The results showed that 12 items of learning instrument of learning progression in the concept of biodiversity are categorized as valid and reliable with low values of validity and reliability. The level of difficulty of the items included in the medium category. Distinguishing power of 12 items, 5 of them included in the bad category, namely questions number 1, 2, 3, 6, and 10. The results of the concept understanding profile were reviewed from class, both levels were in accordance with their level with the percentage of the number of class X students of 40 , 8% and class XI of 44.5% who answered at level 4. The results of understanding the concept in terms of gender are the percentage of the number of male students is slightly higher than the female student, which is equal to 46.9% in male students and 46 , 3% were female students.